Bentuk dan Makna Nomina Dalam Lagu Pop Manado - Nebath, Novie (Kajian Linguistik, 2016)
Manadonese malay is a varian of malay. It spread to all over the country especialy North Sulawesi. It has the function of communication tool in daily activities specialy in manadonese popular songs. Noun is one of the word classes that exist in grammar point of view. It has the function as subject or object of the clause. In the popular manadonese songs, the form and the meaning can be seen from the form of the words. Keywords: noun, malay, popular songs